Resenha do livro "As cidades no tempo" - Silva, Maria Aparecida de Oliveira (Revista Eletrônica História em Reflexão, 2009)
CARVALHO, Margarida Maria; LOPES, Maria Aparecida de S. e FRANÇA, Susani Silveira Lemos (Orgs.). As cidades no tempo. Franca/São Paulo: UNESP/Olho d’Água, 2005. 323 p.